Europe's Encounter with Islam : the Secular and the Postsecular. - Mavelli, Luca (Interventions., 2012)
In the last few years, the Muslim presence in Europe has been increasingly perceived as 'problematic'. Events such as the French ban on headscarves in public schools, the publication of the so-called 'Danish cartoons', and the speech of Pope Benedict XVI at the University of Regensburg have hit the front pages of newspapers the world over, and prompted a number of scholarly debates on Muslims' capacity to comply with the seemingly neutral and pluralistic rules of European secularity. Luca Mavelli argues that this perspective has prevented an in-depth reflection on the limits of Europe's secula.